PEMBUATAN SIMULASI ALL TERRAIN VEHICLE PADA DUNIA VIRTUAL - Andreas Sutantra (Jurnal Infra, 2014)
The making of this simulation is to facilitate someone studying the early stages of how to control the special vehicles without need to face the risk of an accident. The simulation of land vehicles / off road car (All Terrain Vehicle) made, having some simple features like walks in rocky and bumpy road. The software use Logitech Steering Wheel or Keyboard as the controller. This simulator game is made using PhysX to make it easier when incorporating physics in the real world into the virtual world. Logitech SDK, derived from Logitech Gaming Software, is needed for data input from Logitech steering wheel. The result of this thesis is the data such as car position with coordinates x, y, z, and the speed of the car that will be used to control the MA3I platform. This output is affected by some input from the user in the form of gas, brake, and steering wheel.